3x^2 = 11x + 4
3x^2 - 11x - 4 = 0
(2 numbers to multiply to (3)(-4) = -12 and add to -11): -12, 1
3x^2 - 12x + x - 4 = 0
3x (x - 4) + (x - 4) = 0
(3x + 1)(x - 4) = 0
3x+1 = 0
x = -1/3
x - 4 = 0
x = 4
2.
x^2 + 12x + 32 = 0
(2 numbers that multiply to 32 and add to 12) : 8, 4
(x + 8)(x + 4) = 0
x = -8
x = -4
2007-02-04 15:20:56
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Rewrite the first one:
3x^2 - 11x - 4 = 0
factor it: (3x+1)(x-4)=0 so that x=-1/3 or +4
You can also use the quadratic formula, but factoring, when it is fairly easy is easier with fewer steps...if you can see the factors easily...on a test, don't waste time on it if you don't see it immediately and use the quad
x^2 + 12x +32 = 0
(x+8)(x+4) = 0 and x=18,-4
This one was really easy
I hope that I have helped you
2007-02-04 23:24:41
·
answer #2
·
answered by kellenraid 6
·
0⤊
0⤋
OK so lets go back to the quadratic equation formula:
if your quadratic equation is in the form
ax^2 + bx +c = 0
Then you can use the fomula
x = (-b + Squareroot(b^2 - 4ac)) / 2a
x = (-b - Squareroot(b^2 - 4ac)) / 2a
(see a cleaner version below)
http://en.wikipedia.org/wiki/Quadratic_equation
Find out what a b and c are and plug them into the quadratic equation formula.
In the first problem, try rewriting that thing to look like
ax^2 + bx + c = 0
by rearranging the terms.
For the second one, its already in that form so just plug it in. There is no 'a'! you may say. Its just x^2!!
ah but remember that x^2 is the same as 1x^2, so a = 1 in this case.
2007-02-04 23:24:47
·
answer #3
·
answered by baldukakis 2
·
0⤊
0⤋
Make one side of the equation zero.
Then factor the other side.
3x^2 = 11x + 4
3x^2 - 11x - 4 = 0
(3x + 1)(x - 4) = 0
3x = 1
x = 1/3
x = 4
Question 2: Just factor
(x + 4)(x + 8) = 0
x = -4
x = -8
2007-02-04 23:21:22
·
answer #4
·
answered by ecolink 7
·
0⤊
0⤋
3x^2=11x+4
3x^2-11x-4=0
substitute numbers into the quadratic equation:
a=3
b=-11
c=-4
x=4 or x= -1/3
x^2+12x+32=0
substitute numbers into the quadratic equation:
a=1
b=12
c=32
Answer: x= -4 or x=-8
Email me if you need the work shown...
2007-02-04 23:27:37
·
answer #5
·
answered by mrb1017 4
·
0⤊
0⤋
3x^2 = 11x + 4 subtract 11x+4 from each side
3x^3-11x-4=0
(3x+1)(x-4)=0
3x+1=0
3x=-1
x=-1/3
x-4=0
x=4
roots are x=4, -1/3
x^2 + 12x + 32 = 0
(x+8)(x+4)=0
x+8=0
x=-8
x+4=0
x=-4
roots are x=-4, -8
2007-02-04 23:58:39
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
set up the first equation to be in standard form
3x^2-11x-4=0
a=3
b=-11
c=-4
remember the formula? -b+ or - rad b^2 - 4ac all over 2a
substitute:
-(-11) +or - rad (-11)^2 -4(3)(-4) all over 2(3)
can you finish it?
The other is already in standard form, and easier since you have no double negs to bother with.... Helpful?
If I didn't make any screwy mistakes, the ans to the first one is
11+ or - rad 121+48 all over 6
11 + or - rad 169 all over 6
11 + sq rt of 169 all over 6
11 + 13 all over 6
24 over 6 or
4
and finish with subtracting rad (sq. rt of 169) 13 all over 6
or -1/3 so it has two answers, since, as you know, x is squared
2007-02-04 23:28:06
·
answer #7
·
answered by April 6
·
0⤊
0⤋